2004
DOI: 10.1044/0161-1461(2004/017)
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception Benefits of FM and Infrared Devices to Children With Hearing Aids in a Typical Classroom

Abstract: This information can assist in making S/N-enhancing device decisions for students using hearing aids. In a reverberant and noisy classroom setting, classroom sound field devices are not beneficial to speech perception for students with hearing aids, whereas either personal FM or desktop sound field systems provide listening benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 30 publications
2
58
0
6
Order By: Relevance
“…Apesar do HINT Brasileiro não disponibilizar uma versão do teste para crianças como em outras Línguas (Hearing in Noise Test for Children /HINT-C) (23,24), muitos estudos utilizam o HINT com essa população (6,(25)(26)(27), visto que o material de fala desenvolvido para o teste busca metodologicamente controlar as variáveis que podem influenciar a inteligibilidade de fala para adultos e crianças (11).…”
Section: Discussionunclassified
“…Apesar do HINT Brasileiro não disponibilizar uma versão do teste para crianças como em outras Línguas (Hearing in Noise Test for Children /HINT-C) (23,24), muitos estudos utilizam o HINT com essa população (6,(25)(26)(27), visto que o material de fala desenvolvido para o teste busca metodologicamente controlar as variáveis que podem influenciar a inteligibilidade de fala para adultos e crianças (11).…”
Section: Discussionunclassified
“…In an ideal room, both systems were similar, and only for the poor environment, the desktop FM system was the most effective one in terms of speech perception due to the proximity of the microphone and the CI Anderson and Goldstein (12) . Participants presented better speech recognition with the three types of amplification system.…”
Section: United Statesmentioning
confidence: 94%
“…Although ear-level FM provides the better signal-to-noise ratio as compared with sound-field options, 48 this choice of FM coupling may not always be the most practical based on the needs of the child. As is the case with personal amplification, choices for FM need to be made on an individual basis considering the environment in which the device will be used, age of the child, degree and configuration of hearing loss, and use of a hearing aid.…”
Section: Conventional Technologymentioning
confidence: 99%
“…Anderson and Goldstein 48 found that classroom amplification systems did not provide benefit beyond that of the children's personal hearing aids. In situations where there is a classroom amplification system in place, a trial with ear-level FM may be recommended.…”
Section: Conventional Technologymentioning
confidence: 99%